The Effect Of Pregnancy Class On Anxiety In Primigravid Mothers In The Second And Third Trimesters In The Working Area Of The Kota Wilayah Utara Community Health Center Kediri City - Abolla, Yeni (Universitas STRADA Indonesia, 2016)
Pregnancy is a condition where a woman has a fetus growing inside her body (generally in the womb) for a period of around 40 weeks or 9 months, calculated from the start of the last menstrual period until delivery. The aim of this research is to analyze the influence of pregnant women's classes on anxiety in primigravida mothers in the second and third trimesters in the Working Area of the City Health Center in the Northern Region of Kediri City. There were 13 respondents in this study. It is known in this study that there is a significant difference in the level of anxiety before and after the implementation of the class for pregnant women. These results were proven by the Wilcoxon test with a value of p = 0.001 < α = 0.05 where H0 was rejected and H1 was accepted which stated